Effects of water and weed management on the weed density, grain yield, and water productivity of wet-seeded rice - Samoy-Pascual, Kristine; Ariola, Christian Paul; Martin, Edwin C. (2020)
Shifting from conventional transplanting to direct seeding of rice is an alternative option to save irrigation water and reduce labor cost. Weeds are one of the major challenges in direct seeding. Field experiments in split-plot design were conducted to evaluate the effects of different water and weed management modes on the weed density, grain yield, and water productivity of direct wet-seeded rice during two dry seasons (DSs) in Nueva Ecija, Philippines. Three water management (W) modes were used: continuous flooding (CF); safe alternate wetting and drying (AWD); and modified CF (mCF). The four weed management (M) modes were: unweeded (UW); hand-weeding at 21 and 42 days after seeding [DAS] (HW); application of pre-emergence herbicide [pretilachlor] at 5 DAS (PR); and application of post-emergence herbicide [bispyribac sodium] at 15 DAS (PO). M modes showed significant effects (p < 0.05) on the weed density and grain yields in both years, with UW obtaining the lowest grain yield and highest weed density. No significant differences in grain yields were noted among weed control treatments. They only increased grain yields by 18?52% relative to UW. HW and PR treatments showed maximum yields. The W modes did not affect the grain yields nor the weed density, but water productivity was highest in AWD in both years. The higher grain yield and lower total water input in AWD maximized water productivity relative to the conventional practice of CF. (Author's abstract)